Experimental Challenges of the First Mass Measurement Campaign at the Rare-RI Ring. (December 2020) - Naimi, S.; Li, H.F.; Abe, Y.; Yamaguchi, Y.; Nagae, D.; Suzaki, F.; Wakasugi, M.; Arakawa, H.; Dou, W.; Hamakawa, D.; Hosoi, S.; Inada, Y.; et al.
Abstract: With the recent commissioning of the Rare-RI Ring (R3), nuclear mass measurement of rare isotopes (RIs) produced at the RI Beam Factory (RIBF) at RIKEN has become possible. The R3 spectrometer is based on the Isochronous Mass Spectrometry technique that allows for reaching a mass measurement precision of 10 −6 within less than 1 ms. With the newly established self-triggered individual injection method, R3 specialized in mass measurements of extremely short-lived nuclei with low production yields. In this paper, we report the first mass measurement campaign conducted at the R3 addressing nuclei in the vicinity of N=50 and N=82 neutron magic numbers, with a particular focus on the challenges of this new facility.